Geostrategy from the far right: How Eurosceptic and far-right parties are positioning themselves in foreign and security policy - Max Becker; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2024)
Far-right parties are gaining support across Europe. Their level of participation in national governments is increasing, and they are expected to make further gains in the European Parliament elections in June 2024. As their influence over European Union (EU) policy rises, it is imperative to assess how they are positioning themselves on crucial dimensions of EU foreign and security policy. A closer look shows that geostrategic issues remain a cleavage point that is contributing to the fragmentation of the far-right spectrum. Their positions fluctuate between a transatlantic orientation and clear support for Ukraine among the national-conservative European Conservatives and Reformists (ECR), to fundamental opposition with an anti-Western stance among parts of the right-wing populist to extremist parties in the Identity and Democracy (ID) Group. Due to the intergovernmental nature of EU foreign and security policy, the biggest challenges will come with national elections and coalition-making.
Keywords: 320; European Union; EU; European Parliament; European Parliament elections 2024; European elections 2024; far-right parties; EU foreign and security policy; European Conservatives and Reformists; ECR; Identity and Democracy; ID; Fidesz; EU relations with Russia; EU relations with China; EU relations with the United States; EU relations with NATO; enlargement of the EU; CFSP; CSDP; voting behaviour; geostrategic positioning; fragmentation of the far-right spectrum